Evaluation of Patient IgM and IgG Reactivity Against Multiple Antigens for Improvement of Serodiagnostic Testing for Early Lyme Disease - Brandt, Kevin S.; Horiuchi, Kalanthe; Biggerstaff, Brad J.; Gilmore, Robert D. (Frontiers in Public Health, 2019)
2729 Serologic testing is the standard for laboratory diagnosis and confirmation of Lyme disease. Serodiagnostic assays 28 to detect antibodies against Borrelia burgdorferi, the agent of Lyme borreliosis, are used for detection of infection. reliable in the later 2930 stages of infectionH, however, serologic testing within the first month of infection is less sensitive as 3031 patients’ antibody responses continue to develop. Previously, we screened several B. burgdorferi in 3132 vivo expressed antigens for candidates that elicit early antibody responses in patients with Stage 1 and 2 3233 Lyme disease. We evaluated patient IgM seroreactivity against 6 antigens and found an increase in 3334 sensitivity without compromising specificity when compared to current IgM second-tier immunoblot 3435 scoring. In this study, we continued the evaluation using a multi-antigen panel to measure IgM plus IgG 3536 seroreactivity in these early Lyme disease patients’ serum samples. Using two statistical methods for 3637 calculating positivity cutoff values, sensitivity was 70% and 84-87%, for early acute and early 3738 convalescent Lyme disease patients respectively. Specificity was 98-100% for healthy non-endemic 3839 control patients, and 96-100% for healthy endemic controls depending on the statistical analysis. We 3940 conclude that improved serologic testing for early Lyme disease may be achieved by the addition of 4041 multiple borrelial antigens that elicit IgM and IgG antibodies early in infection.